Pengujian Model Pengaruh Tata Kelola TI Terhadap Transformasi Digital dan Kinerja Bank A - Trias Zulfa Nurafifah; Rahmat Mulyana; Lukman Abdurrahman (Journal of Information System Research (JOSH), 2022)
The disruption of the latest technology, changes in stakeholder behavior, and the COVID-19 pandemic forced incumbent organizations to digital transformation (DT). In fact, there are still many failed DT investments due to a lack of IT governance practices (ITG). Previous research shows the contribution of ITG in realizing the benefits of IT investment. This traditional ITG mechanism is thought to be not necessarily effective in the digital era. There is still little research on the influence of ITG on DT and Organizational Performance (OP). Therefore, this study examines the model of the effect of hybrid ITG, namely agile/adaptive and traditional on DT and the effect of DT on OP. The method used is a survey by distributing online questionnaires to 11 important roles related to DT and succeeded in getting 54 respondents. Data analysis using Structural Equation Modeling (SEM) approach assisted by SmartPLS. The results showed that the hybrid ITG mechanism, both agile/adaptive and traditional, had a significant positive effect on DT and DT also had a significant positive effect on OP Bank A's. This research contributes as a reference for similar research and can be a reference for implementing the ITG mechanism for the success of DT and the achievement of OP in organizations in general, especially the banking industry.